Association of physical activity and heart failure with preserved vs. reduced ejection fraction in the elderly: the Framingham Heart Study - Kraigher-Krainer, Elisabeth (Oxford University Press, 2013)
AIMS: Reduced physical activity is associated with increased risk of heart failure (HF) in middle-aged individuals. We hypothesized that physical inactivity is also associated with greater HF risk in older individuals, and examined if the association was consistent for HF with preserved ejection fraction (HFPEF) vs. HF with a reduced ejection fraction (HFREF). METHODS AND RESULTS: We evaluated 1142 elderly participants (mean age 76 years) from the Framingham Study without prior myocardial infarction and who attended a routine examination when daily physical activity was assessed systematically with a questionnaire. A composite score, the physical activity index (PAI), was calculated and modelled as tertiles, and related to incidence of HF, HFPEF, and HFREF on follow-up using proportional hazards regression models adjusting for age and sex, and then additionally for standard HF risk factors. Participants with HF and EF <45% vs. ≥45% were categorized as HFREF and HFPEF, respectively. On follow-up (mean 10 years), 250 participants developed HF (108 with HFPEF, 106 with HFREF, 36 with unavailable EF). In age- and sex-adjusted models, the middle and highest PAI tertiles were associated with a 15–56% lower risk of any HF, of HFREF, and of HFPEF, with a graded response across tertiles. In multivariable models, the association of higher PAI with lower risk of any HF and with HFPEF was maintained, whereas the association with HFREF was attenuated. CONCLUSIONS: Our study of an older community-based sample extends to the elderly and to HFPEF previous findings of a protective effect of physical activity on HF risk.